2018
DOI: 10.1073/pnas.1804005115
|View full text |Cite
|
Sign up to set email alerts
|

Two novel protein O -glucosyltransferases that modify sites distinct from POGLUT1 and affect Notch trafficking and signaling

Abstract: The Notch-signaling pathway is normally activated by Notch-ligand interactions. A recent structural analysis suggested that a novel -linked hexose modification on serine 435 of the mammalian NOTCH1 core ligand-binding domain lies at the interface with its ligands. This serine occurs between conserved cysteines 3 and 4 of Epidermal Growth Factor-like (EGF) repeat 11 of NOTCH1, a site distinct from those modified by protein-glucosyltransferase 1 (POGLUT1), suggesting that a different enzyme is responsible. Here,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
85
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(86 citation statements)
references
References 38 publications
1
85
0
Order By: Relevance
“…The mammalian Notch signaling pathway can be regulated by O-glucosylation of EGF repeats of Notch receptors [16]. Takeuchi et al [11] demonstrated the transfer of O-glucose to Notch 1 receptor EGF 11 and Notch 3 EGF10 by either KDELC1 or KDELC2 but not to the Notch 2 receptor. In this study, we successfully proved that KDELC2 knockdown could interrupt KDELC1 expression, which implied that KDELC2 might have some regulations to KDELC1.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The mammalian Notch signaling pathway can be regulated by O-glucosylation of EGF repeats of Notch receptors [16]. Takeuchi et al [11] demonstrated the transfer of O-glucose to Notch 1 receptor EGF 11 and Notch 3 EGF10 by either KDELC1 or KDELC2 but not to the Notch 2 receptor. In this study, we successfully proved that KDELC2 knockdown could interrupt KDELC1 expression, which implied that KDELC2 might have some regulations to KDELC1.…”
Section: Discussionmentioning
confidence: 99%
“…NECD comprises abundant surface-modified O-linked glycans, including O-glucose (O-Glc), O-fucose (O-Fuc), and O-GlcNAc [8,10]. These modifications strengthen the linkage between the Notch receptor and ligands and activate Notch signaling [11]. Initially, Notch receptors enter the endoplasmic reticulum (ER) and Golgi apparatus (Golgi) and are modified by some glycans and glycosyltransferases, including Rumi, Pofut1, O-glucosyltransferase 1 (Poglut1), Poglut2 (KDELC1), and Poglut3 (KDELC2) [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Takeuchi and colleagues also identified two novel O -glucosyltransferases, POGLUT2 and POGLUT3, which are responsible for the transfer of UDP-glucose on the 11th EGF repeat on serine 435, a distinct site from that of POGLUT1 [ 17 ]. Mutations occurring in Ser435 affect the NOTCH1 cell-surface presentation and, consequently, its activation upon interaction with Dll1 [ 28 ].…”
Section: From Golgi To the Cell Membranementioning
confidence: 99%
“…or O-fucosylation C 2 XXXX(S/T)C3 [88,129,130] consensus sequences (the superscript indicates the Cys residue within the EGF-like domain).However, recent studies uncovered new O-glucosyltransferases that can O-glucosylate Ser residues between the 3 rd and 4 th Cys of EGF-like domains[131], precisely where we map the new EGF-like 2 Hex1Pent2 O-glycan in rFIX. In fact, human Coagulation Factor X is O-glucosylated at S 106 in the EGF-like 2 domain, also between the 3 rd and 4 th Cys residues and in a position equivalent to the S 102 residue in rFIX[132].…”
mentioning
confidence: 97%